Vascular Engorgement of Lacrimal Gland Associated With Port-Wine Stain. Issue 4 (July 2016) - Talcott, Katherine E.; Lee, Nahyoung Grace; Freitag, Suzanne K.
Abstract : Port-wine stains are congenital dermal capillary malformations that typically involve the head and neck. While most of them are isolated malformations, they have been associated with other vascular findings, including conjunctival, episcleral, and choroidal hemangiomas. They have also been associated with the phakomatosis Sturge–Weber syndrome, characterized by parieto-occipital, leptomeningeal, and ocular choroidal vascular malformations. However, vascular engorgement of the lacrimal gland has not been previously reported in association with port-wine stains. The authors present a case of a 52-year-old man with a long-standing and isolated right periorbital port-wine stain referred for lacrimal gland enlargement on CT scan. He was found to have asymptomatic right lacrimal gland vascular engorgement, which was radiographically stable over a period of 5 years. Abstract : A 52-year-old man with history of right forehead and periorbital port-wine stain but not Sturge-Weber syndrome was found clinically and radiographically to have associated vascular engorgement of the right lacrimal gland.